Krwawienie podpajęczynówkowe z pękniętego tętniaka - epidemiologia, czynniki ryzyka, objawy, diagnostyka = Subarachnoid hemorrhage from ruptured aneurysm - epidemiology, risk factors, symptoms, diagnosis - Woźniak, Kamila; Ratuszek-Sadowska, Dorota; Śniegocki, Maciej (Journal of Education, Health and Sport, 2016)
Woźniak Kamila, Ratuszek-Sadowska Dorota, Śniegocki Maciej. Krwawienie podpajęczynówkowe z pękniętego tętniaka - epidemiologia, czynniki ryzyka, objawy, diagnostyka = Subarachnoid hemorrhage from ruptured aneurysm - epidemiology, risk factors, symptoms, diagnosis. Journal of Education, Health and Sport. 2016;6(9):255-260. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61657 http://ojs.ukw.edu.pl/index.php/johs/article/view/3801 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016. Krwawienie podpajęczynówkowe z pękniętego tętniaka - epidemiologia, czynniki ryzyka, objawy, diagnostyka Subarachnoid hemorrhage from ruptured aneurysm - epidemiology, risk factors, symptoms, diagnosis Kamila Woźniak1, Dorota Ratuszek-Sadowska2, Maciej Śniegocki1 1. Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2. Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Streszczenie SAH (krwawienie podpajęczynówkowe) to wynaczynienie się krwi z pękniętego, zmienionego naczynia (tętniaka) do przestrzeni podpajęczynówkowej mózgowia i/lub rdzenia kręgowego. W oparciu o dane z piśmiennictwa szacuje, że krwawienie podpajęczynówkowe jest przyczyną około 10 – 12 % wszystkich śródczaszkowych incydentów naczyniowych. Częstość jego występowania wynosi około 6 – 7osób/100 000/rok. Krwawienie podpajęczynówkowe występuje przeważnie u pacjentów w średnim wieku (50. rok życia). Szacuje się, że ok 15 % pacjentów umiera zanim dotrze do szpitala. Nieleczone krwotoki podpajęczynówkowe są przyczyną wysokiej śmiertelności, dlatego tak ważne z punktu widzenia klinicznego jest szybkie postawienie diagnozy i wdrożenie odpowiedniego leczenia. Słowa kluczowe: SAH, krwawienie podpajęczynówkowe, tętniak. Abstract SAH (subarachnoid hemorrhage) is the extravasation of blood from ruptured, amended vessel (aneurysm) in the subarachnoid space of the brain and / or spinal cord. Based on data from the literature it estimates that subarachnoid hemorrhage is the cause of about 10 – 12 % of all intracranial vascular events. Its incidence is about 6 - 7 persons / 100 000 / year. Subarachnoid hemorrhage occurs predominantly in patients in middle age (50 years of age.). It is estimated that approximately 15 % of patients die before reaching the hospital. If left untreated, subarachnoid hemorrhages are the cause of high mortality, so it’s important from the clinical point of view is a fast diagnosis and implementation of appropriate treatment. Key words: SAH, subarachnoid hemorrhage, aneurysm.